Efficacy and safety of a unique enteric-coated bicarbonate-buffered pancreatic enzyme replacement therapy in children and adults with cystic fibrosis. (August 2013) - Konstan, Michael W; Accurso, Frank J; Nasr, Samya Z; Ahrens, Richard C; Graff, Gavin R
Background: Pancreatic enzyme replacement therapy (PERT) is used to treat exocrine pancreatic insufficiency in cystic fibrosis.Results/Methods: Efficacy and safety of a unique enteric-coated (EC) bicarbonate-buffered PERT product (PERTZYE ® /PANCRECARB ® ; Digestive Care, Inc., Bethlehem, PA, USA) was studied in a randomized, double-blind, placebo-controlled cross-over design. Subjects were stabilized on EC-bicarbonate-buffered PERT and a high-fat diet. During two treatment periods, subjects were randomized to EC-bicarbonate-buffered PERT or placebo, followed by a 72-h stool collection employing an ingested stool dye marker. Mean coefficient of fat absorption with EC-bicarbonate-buffered PERT was 82.5% compared with 46.3% with the placebo (absolute difference 36.2%; p < 0.001), a 78.2% improvement for active over placebo. Similar improvements in nitrogen absorption were observed. Overall stool frequency and stool weight decreased (p < 0.001). No safety concerns were identified.Summary: EC-bicarbonate-buffered PERT is effective in treating cystic fibrosis-associated exocrine pancreatic insufficiency.